Discriminação estética sob o enfoque do direito constitucional do trabalho - Muniz, Samuel Levy Pontes Braga (2023)
The present thesis analyzed aesthetic discrimination and its legal impacts on private employment relationships, under the focus of fundamental social rights. The thesis was divided into three main sections. In the first, we present the adopted epistemological assumptions and discussed equality as a fundamental human right. We also tackled the historical premises about the relationship between the fundamental principle of equality and labor rights, as well as examined the right to non-discrimination. In addition, the first chapter categorizes discrimination into various subtypes, including negative and positive, direct and indirect, as well as explicit, disguised and implicit. The second section of the thesis defines the term 'aesthetic discrimination', encompassing concepts such as beauty and ugliness, discussing aesthetics as interpreted by classical and modern Western philosophers, reflecting on the contributions of contemporary sociology to the topic, identifying the peculiarities of aesthetic discrimination in the legal context, and exploring the relationship between appearance, autonomy of will, and work. In the third chapter, the research focuses on aesthetic discrimination in the context of substantive labor law, analyzing the right to decent work, personality rights, legal protection in the work environment, and the limitations of the employer's power over the employee. Additionally, the implications of aesthetic discrimination in relation to contract termination and corresponding compensations are discussed, presenting possible scenarios of unlawful actions committed by the employer and the employee. We also examined the issue of non-material damage, followed by an analysis of collective aesthetic discrimination, observing how prejudices and stereotypes based on appearance can affect groups of workers. In conclusion, the third chapter, the study turns to the intersectionality of aesthetic and racial discrimination. At the end, we sought to answer the starting question of the research: is there a fundamental right to non-aesthetic discrimination within the scope of typical subordinate labor relations in the Brazilian legal system?